Strategi Komunikasi Komunitas Rumah Bergerak dalam Membentuk Perilaku Kreatif Anak Muda - Rafiko Rahman; Kartika Suci Lestari Parhusip (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The communication strategy and community strategies are so important in creating the creative behavior of young people. A creativity does not come itself but from innerself or from the circles. The author chooses these problems with the aim of looking the communication strategies and the Rumah Bergerak community to have a role in creating the creative behavior of young people. This study using a theoretical study of communication strategies, group communication, creative behavior. In this study, the author used a qualitative approach with a type of descriptive research, also by using the constructivism paradigm. The author also have interviewed with four informants as resource persons, consisting of the Founder, PIC of the Klab Semu, PIC Gravis, PIC Kulak Kulik Kamera and also observed the Rumah Bergerak community. The results of this study shows that young people who are members of this community can be creative by produce a creation through a communication strategies of young people.